Antibacterial Activity and Phytochemical Screening of The Fraction of Endophytic Fungus Derived from Sambiloto Flowers (Andrographis paniculata (Burm.f.) Nees) - Firda Febria; Suryelita Suryelita; Riga Riga (Universitas Nusa Bangsa, 2022)
Sambiloto is one of the plants in Acanthaceae family obtaining antibacterial compounds. Another source to identify the antibacterial compounds from sambiloto is endophytic fungus. The study aimed to observe the antibacterial activity and phytochemical constituents of the fractions of endophytic fungus isolated from sambiloto flowers (Andrographis paniculata (Burm.f.) Nees). Endophytic fungus was extracted using ethyl acetate to give the crude extract. The crude extract was fractioned by Vacuum Liquid Chromatography (VLC) using hexane-ethyl acetate as the solvents to give 17 fractions. In addition, 7 fractions were created by combining the identical stain patterns on the chromatograms. The phytochemical composition of the isolate fraction has been tested, and it was proven that it contained terpenoid and steroid components. The antibacterial activity of the 7 fractions was also examined using the disc diffusion method with a concentration of 5%. The semi-polar fraction actively inhibits bacterial growth.Keywords: antibacterial; Andrographis paniculata; fractination; phytochemical; endophytic fungus ABSTRAKAktivitas Antibakteri dan Kandungan Fitokimia dari Fraksi Jamur Endofitik pada Bunga Sambiloto (Andrographis paniculata (Burm.f.) Nees)Sambiloto adalah salah satu tanaman dalam famili Acanthaceae yang dilaporkan menghasilkan senyawa antibakteri. Sumber lain untuk mengidentifikasi senyawa antibakteri dari tumbuhan sambiloto adalah jamur endofitik. Tujuan dari penelitian ini adalah mengamati aktivitas antibakteri serta kandungan fitokimia dari fraksi jamur endofitik pada bunga sambiloto (Andrographis paniculata (Burm.f.) Nees). Jamur endofitik diekstraksi dengan etil asetat dan menghasilkan ekstrak pekat. Ekstrak pekat difraksinasi menggunakan metode Kromatografi Cair Vakum (KCV) menghasiilan 17 fraksi. Berdasarkan analisis noda pada kromatogram, fraksi tersebut digabungkan sehingga diperoleh tujuh fraksi. Ketujuh fraksi tersebut diuji kandungan fitokimianya yang menunjukkan positif mengandung senyawa terpenoid dan steroid. Ketujuh fraksi juga diuji aktivitas antibakteri menggunakan metode difusi cakram dengan konsentrasi ekstrak 5% . Fraksi yang bersifat semipolar lebih efektif menghambat pertumbuhan bakteri.Kata kunci: Andrographis paniculata; antibakteri; fitokimia; fraksinasi; jamur endofitik